Use of suction caissons for seawall construction - Chen, Hao (2023)
With rising sea level and demand for more nearshore infrastructures, the current methods for seawall construction may no longer be sustainable. Alternative seawall construction methods need to be developed. When seawall or other coastal defense systems are constructed on soft marine deposits, suction caissons are feasible to be installed into marine clay layer as foundations. Using suction caissons as part of the foundation for seawall might offer a more economical solution when the water depth is relatively deep. A conceptual design and related construction procedure for the seawall constructed on suction caisson foundation is proposed in this paper for a land reclamation project. The design issues for the seawall constructed on soft marine deposits are discussed. An analytical method for analyzing the stability of the seawall on suction caisson foundation is also proposed based on a limit equilibrium method. The proposed analytical method is verified using Plaxis 2D finite element analysis (FEA) which has been verified using model tests of suction caisson in soft clay beforehand. The results from the finite element simulation are consistent with those from the analytical method. The horizontal deflection of seawall is about 1/75 of the seawall height.